Menghitung Kebutuhan Rak Penyimpanan Berkas Rekam Medis Pasien Berdasarkan Aspek Antropometri Petugas Rekam Medis Di Rsud Kota Yogyakarta - Gani, Mahrizal Ramadhan Abdul; , Ibnu Mardiyoko, SKM., M; , Tanjung Anitasari I.K., SKM., M.Kes (2017)
Permenkes 269 year 2008 article 7 states that health rvices are required to provide the necessary facilities in the context of conducting medical records. The availability of storage shelves at RSUD Kota Yogyakarta is still less due to the capacity of the medical record file that exceeds the capacity and the design of the shelf size is not in cordance with the size dimensions of the officer's body so that officers complain of muscle fatigue. The purpose of this research is to know the condition of storage room of medical record file, to analyze anthropometry data of medical record officer at RSUD Kota Yogyakarta and to calculate storage rack needs for next five years. This research is a scriptive research with cross sectional design. The sample of this research is the new medical record file of ambulatory care, emergency unit, and inpatient unit in 2014-2016 as many as 383 files from the total population 177,872 files taken by simple random sampling technique and medical record officer as much as 35 people from total population 39 people taken by purposive technique Sampling. Data collection through interviews and measurements of body dimensions. The results showed that the storage shelf needs in RSUD Kota Yogyakarta for the next five years as many as 14 shelves with high rack 1.8 meter shelf design, 1.6 meters rack length and the distance between shelves is 66 centimeters